News website users in Mexico: factors influencing their loyalty - Dávila Garza, Horacio; Alarcón Martinez, Gustavo Juan; López Pérez, Jesús Fabián (2023)
Recent technological advances have significantly impacted news media in the way they provide news to the public, evolving into a digital environment. Therefore, digital media today focuses on generating readers’ loyalty to their news websites. In this sense, a multiple linear regression analysis was carried out on a sample of 344 surveys of adult residents in the cities of Mexico and Monterrey. The results show that factors such as familiarity, satisfaction and reputation are positively related to the loyalty of news website users. However, they also show that the importance of the impact of these factors is different when the analysis is carried out in a stratified manner, such as residence, gender or education, which allows us to conclude that digital media can guide their loyalty efforts depending on the profile of their readers and the market they seek to target. To illustrate focusing on stratification by place of residence, the most significant factors for the Mexico City group corresponded to familiarity and satisfaction, wile for the Monterrey group the most significant factors were reputation and familiarity in that order. Results with this type of differences between groups were also obtained when comparing by gender and schooling. It is recommended for future research on the subject, to include other cities within the country, with the purpose of contrasting these paper’s findings.